Perbandingan Radiasi Sinar UV Pada Pelaksanaan Praktik Pengelasan (SMAW) Di Fakultas Kemaritiman UNISVET Dengan Peralatan Sterilisasi Corona Virus 19 - Kurniawan, Ratna Dwi; S, Rudy (Marine Science and Technology Journal, 2021)
Covid19 has changed the behavior of the world's people, until the whole world is affected, schools, offices, public places are closed, restrictions on activities, this condition forces scientists to be extra hard to create inventions to overcome these problems. Medicines to treat it have not yet been found, but several vaccines have been found, but whether the effectiveness of the vaccines can really overcome the pandemic, then efforts that can be done are to minimize the spread of the corona virus. Apart from medicine and vaccines, research is also being conducted on the equipment that can be used to kill viruses. Equipment with UV light has been widely offered and even sold freely, even though the use of UV can not be arbitrary because it can cause irritation. In welding that also emits harmful UV radiation, with a current of 150 -200A, Radiation ranges from 0.87-3.2 W / m2 far beyond the allowable limit of 0.001W / m2, while that of the steilization equipment ranges from 2.8 W / m2 By looking at this comparison, can the implementation of welding practices on campus be said to be safe? Because the UV emission from welding the value is like that used in sterilization equipment.